Flipped Classroom with Guided Inquiry on Buffer Solutions via Discord: A Study of Learning System Development - Aprilia Silviani Harahap; Mawardi Mawardi; Okta Suryani; Umar Kalmar Nizar; Reza Akmar (Postgraduate, University of Mataram, 2025)
This research aims to design a flipped classroom learning system incorporating guided inquiry, using the Discord platform for buffer solution materials in Phase F. The study employed Plomp Educational Design Research framework, which comprises initial investigation, design, construction, testing, evaluation, and refinement. The product underwent validation through expert evaluation and was assessed for practicality and effectiveness. The content validity achieved a score of 0.89, while the media validity scored 0.90, meaning both belong to the valid category. Evaluation of practicality showed that the system was highly practical, with teachers and students giving it an overall score of 90% and 92% respectively. Effectiveness was measured by analyzing pretest and posttest results using the N-Gain formula, yielding a score of 0.75, which is classified as high gain. The overall findings suggest that the developed learning system is valid, practical, and effective in enhancing students’ understanding of buffer solutions. Moreover, the integration of Discord provides an accessible and interactive digital environment, aligning with the needs of 21st-century education and the Merdeka Curriculum. Therefore, this model can be recommended as an innovative solution for digital chemistry instruction in senior high schools.